Longitudinal surveillance of outpatient β-lactam antimicrobial use in Canada, 1995 to 2010 - Shiona K Glass-Kaastra; Rita Finley; Jim Hutchinson; David M Patrick; Karl Weiss; John Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: β-lactam antimicrobials are the most commonly prescribed group of antimicrobials in Canada, and are categorized by the WHO as critically and highly important antimicrobials for human medicine. Because antimicrobial use is commonly associated with the development of antimicrobial resistance, monitoring the volume and patterns of use of these agents is highly important.